Strengthening urban food systems through engaging with informal sector food vendors: Two models for scaling capacity sharing - Prain, Gordon; Alvarez, S.A.; Bertuso, A.; Sharma, G.; Kawarazuka, Nozomi; Mutua, F.; Ricarte, P. (2025)
This report examines how engaging informal sector food vendors can strengthen urban food systems in the Global South through scalable capacity sharing approaches. Drawing on case studies from Quezon City, Philippines, and Nairobi, Kenya, it presents two models for scaling the Vendor Business School (VBS): a rapid co-creation model with local government and an incremental engagement model in contexts of low institutional trust. The study shows that participatory, gender-responsive capacity sharing can improve food safety, livelihoods, and governance outcomes while supporting more inclusive, resilient, and sustainable urban food systems.